FROM CIVIL WAR TO THE MING FOUNDING: THE VERBAL PHOTOGRAPHY OF LIU SONG. Issue 1 (May 2014) - Dardess, John W.
<x content-type="archive" xml:space="preserve">Abstract</x> A nearly forgotten poet, writer, and early Ming official, Liu Song tells us straightforwardly and vividly what life was like for him during the wars of the 1350s and 1360s in Jiangxi, and in Ming government in Nanjing and the future Beijing during the 1370s and early 1380s. His views of the war years were mainly negative, and his experience of the early Ming and his encounters with Taizu were highly positive. He shows us another side of the early Ming, which we usually and rightly describe as repressive and despotic. This article sits at a junction of social, military, political, and literary history.